Techono-Economical analysis of a pv system with energy storage for clients with a residential tarif in Costa Rica - Vega Garita, Víctor (2023)
Solar energy is a type of renewable energy that, due to its nature, it is intrinsically influenced by the variability of meteorological and geographical conditions of the site. To tackle variability, storage technologies such as batteries can be used, they enable the integration of these energies into the electricity network and supply of loads at times of low generation. In this paper, a technical and economic analysis of a photovoltaic (PV) system including energy storage is carried out. Therefore, a model of a photovoltaic system with and without energy storage was developed in order to compare the technical and economic metrics for each case in the context of a residential system, while following a flat tariff. Based on the analysis, the results indicate that from the economic point of view, it is more profitable to install systems operating only with PV modules. On the other hand, the systems with pv system and storage allows a better use of the photovoltaic energy as can be seen from the metrics of self-consumption and autarky. Thus, this article contributes to the analysis of photovoltaic systems with energy storage through batteries, a relatively new technology in the country, collaborating with the generation of knowledge of systems that are expected to substantially change the electrical system.